(untitled) (Zaporizhzhia Historical Review, 2021)
The article is devoted to the research of the source studies aspects of the theory of hermeneutics experience of H.-G. Gadamer. It has been demonstrated that philosophic hermeneutics doesn’t suggest the universal humanities method of cognition. It characterizes the conditions in which cognition is accomplished. H.-G. Gadamer has demonstrated that scientific method alone does not guarantee the truth, because our existence takes part in cognition